THE EFFICACY OF PROPHYLAXIS OF LYME DISEASE USING ANTIBIOTICS AMONG PEOPLE BITTEN BY IXODID TICKS - T. V. Tunik (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
For the first time the results of the study of 1399 blood serum, samples from people bitten by Ixodid ticks in Predbaykalye region (East Siberia, Russia) and asking for medical care in the Center for prophylaxis of tick-borne diseases of Scientific Center of Family Health. Problems and. Human Reproduction. SB RAMS. The study showed, high, (up to 99,93 %) efficacy of early antibiotic course in preventing the Lyme disease in bitten people